Peran Forum Kerukunan Pemuda Umat Beragama (FKPUB) dalam meningkatkan Moderasi Beragama berbasis Kearifan Lokal bagi masyarakat multi-agama di Madura - Fajar; Andri Sutrisno (Indonesian Journal of Islamic Religious Education, 2023)
This research aims to understand the social construction of the Pamekasan Madura community and the social interactions of the multi-religious society in Pamekasan Madura and analyze the role of the Religious Youth Harmony Forum in implementing local culture in Pamekasan. This research uses a descriptive qualitative approach to the social construction and social interaction paradigm with a case study type of research. Data collection techniques used include observation, interviews, and documentation. This research shows that the social construction built by  Religious Youth Harmony Forum in Pamekasan went through three critical stages: externalization, social interaction, and local wisdom.